Need Analysis for Teaching English in Early Childhood Education Students - Wati, Siska Oktawidya; Ramadhan, Syahrul (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
Analysis of needs for English language teaching in PG-Paud. English for Specific Purposes (ESP) in the learning process in higher education is often less effective. One contributing factor is the lack of a learning plan so that learning is not relevant to the field of science they are capable of. Therefore, it is necessary to start planning learning by conducting a needs analysis based on students' needs in learning English. This research aims to determine and describe the needs of English language students in PG PAUD Universitas Prima Nusantara Bukittinggi. This research was conducted using a qualitative descriptive approach. The objects of this research were students in the third year. Data was collected through questionnaires and direct interviews. The collected data is classified so that students' needs in learning English can be identified, then each one is explained. The research results show that (1) students' mastery of English is still relatively low, (2) 50% of students improve their oral communication or speaking skills and 30% write as the main priority in learning English in preparation for applying for work, (3) during learning English, students expect an increase in their skills related to both oral and written. Based on these results, it is recommended to prepare syllabus planning and develop English teaching materials in PG-Paud programs.